Beyond Rationality: The Role of Anger and Information in Deliberation. (February 2016) - Kim, Nuri
The effects of anger and information were experimentally tested in a small group deliberation setting. The participants were randomly assigned to one of four conditions varying in the level of induced anger and amount of information they received. After reading about a controversial local issue, they engaged in a group discussion about the topic. Content analysis revealed each individual's level of participation. More informed participants expressed more opinions during deliberation than less informed participants. Participants made to feel angry were also more active than those in the control condition, but to a lesser degree than the more informed participants. Structural equation modeling suggested that the effect of anger on postdeliberation argument repertoire and knowledge was more direct, whereas the effect of information was mediated by active participation during deliberation.